A New Acquisition Algorithm with Elimination Side Peak for All BOC Signals. (30th March 2015) - Liu, Fang; Feng, Yongxin
Abstract : A new inhibition side peak acquisition (ISPA) algorithm is proposed for binary offset carrier (BOC) modulated signals, which will be utilized in global navigation satellite systems (GNSS). We eliminate all side peaks of the BOC correlation function (CF) by structuring special sequences composed of PRN code and cycle rectangular sequences. The new algorithm can be applied to both generic sine- and cosine-phased BOC signals, as well as to all modulation orders. Theoretical and simulation results demonstrate that the new algorithm can completely eliminate the ambiguity threat in the acquisition process, and it can adapt to lower SNR. In addition, this algorithm is better than the traditional algorithms in acquisition performance and inhibition side peak ability.